home Art Gallery of Western Australia. - Dodge, Alan R.; Dufour, Gary; Goldblatt, David; Mulcaire, Thomas; Smith, Trevor (Perth : Art Gallery of Western Australia, 2000)
Morris, Sarah ; Geers, Kendell ; Orta, Lucy ; Mthethwa, Zwelethu ; Strba, Annelies ; de Oliveira, Ricardo ; Carver, Raymond ; Glick, Rodney ; Kpobly, Joseph ; Sissako, Abderrahmane ; Diop Mambety, Djibril ; Wall, Jeff ; Igloolik Isuma Productions ; Goldblatt, David ; Ngui, Matthew ; Peljhan, Marko - Projekt Atol
biog. per kunstenaar
Engels
home Art Gallery of Western Australia, Art Gallery of Western Australia, Perth, 5 February - 25 April 2000
boek